The Effect of Murabahah and Mudharabah Financing on Non Performing Financing (NPF) at Bank Syariah Indonesia - Qodari, Amimah; Silvia, Sineba Arli (Institut Agama Islam Negeri (IAIN) Curup, 2022)
This study aims to analyze the effect of murabahah and mudharabah financing on non-performing financing (NPF) of Bank Syariah Indonesia before and after the merger. This study examines the effect of murabahah and mudharabah financing variables on non-performing financing (NPF). The population used in this study are Islamic banks that have merged, namely BNI Syariah, BRI Syariah, and Bank Syariah Mandiri for the period 2017-2021. The sample used in this study is BSI which publishes an annual report in the 2017-2021 period. This research data is secondary data, which was obtained from the website of Bank Syariah Indonesia which became the research sample. While the data analysis method used is multiple linear regression analysis. The results of this study indicate that the murabahah and mudharabah financing variables have an influence on the NPF of 5.4% with a significance level of 0.532. Partially, the murabahah financing variable has an effect and is significant on the NPF of Indonesian Islamic Banks (0.915 > 0.050) and the mudharabah financing variable has a significant effect on the NPF of Indonesian Islamic Banks (0.304 > 0.050).